Feeding Efficiency Using Auto Feeder in Vannamei Shrimp (Litopenaeus vannamei) Cultivation at PT. Bumi Harapan Jaya, Tano Photo, West Sumbawa - Maulana, Rona; dwiyanti, septiana (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Feed is a very important factor because it takes up 60-70% of the total operational costs, so that feed provided according to needs will stimulate optimal growth and development of shrimp production. The use of auto feeder machines can help in providing shrimp feed more effectively and maintaining water quality to remain stable and suitable for vannamei shrimp cultivation. The purpose of this study was to determine the efficiency of feeding in vannamei shrimp ( Litopenaeus vannamei ) cultivation . The method used in this study is the method descriptive, the data analyzed in this study is shrimp growth data obtained from sampling results and water quality data both in the field and laboratory. The results of this study are that the daily growth (ADG) of vannamei shrimp is in the range of 0.22-0.38 grams, this data is already optimal and for the average weight (MBW) obtained 4.56 grams then increased over time to reach DOC 108 with a weight of 24.97 grams. Based on the results of the average weight growth obtained, it is known that the growth is optimal and it is known that the water quality value is still in optimal condition in vannamei shrimp cultivation, both physical and chemical parameters. From this study it is known that feeding using an auto feeder has a good effect on the growth of ADG and MBW shrimp and also the feed given using an auto feeder can minimize feed falling to the bottom so that water quality is maintained and remains in optimal condition for vannamei shrimp cultivation. Keywords: Cultivation, Feed, Vannamei , Auto Feeder, Growth